Nafion-Mercury Coated Film Electrode for the Adsorptive Stripping Voltammetric Determination of Lead and Cadmium in the Presence of Pyrogallol Red - Segura-Segura, R; Segura-Segura, R (2012)
An adsorptive stripping voltammetric (AdSV) method is presented for the simultaneous determination of Pb(II) and Cd(II) at trace levels in natural waters, based on metal complexation with pyrogallol red (PR) and subsequent adsorptive deposition on a Nafion-mercury coated glassy carbon electrode (NHgFE). Pyrogallol red forms complexes with a metal:ligand stoichiometry of 1:1 with Pb(II) and of 1:2 with Cd(II). Optimal analytical conditions were pH 4.0 (acetate buffer); CPR=2.8 ?mol L-1; E ads=-0.40 V vs. Ag/AgCl; tads=100 s. The linear calibration curves ranged from 1.0 ?g L-1 to 16.0 ?g L -1 for Pb(II) and from 1.0 ?g L-1 to 13.0 ?g L -1 for Cd(II). The detection limits (S/N=3) were 0.05 ?g L -1 for Pb(II) and 0.01 ?g L-1 for Cd(II). The relative standard deviation was 1.0% and 2.0% (n=7), respectively, for a solution containing 5.0 ?g L-1 Pb(II) and Cd(II). The method was validated by determining Pb(II) and Cd(II) in certified reference waste water (SPS-WW1). Finally, the method was applied to the determination of Pb(II) and Cd(II) in commercial mineral water samples after UV digestion. © 2012 Elsevier B.V.